2014
DOI: 10.1016/j.snb.2013.10.084
|View full text |Cite
|
Sign up to set email alerts
|

Polydimethylsiloxane core–polycaprolactone shell nanofibers as biocompatible, real-time oxygen sensors

Abstract: Real-time, continuous monitoring of local oxygen contents at the cellular level is desirable both for the study of cancer cell biology and in tissue engineering. In this paper, we report the successful fabrication of polydimethylsiloxane (PDMS) nanofibers containing oxygen-sensitive probes by electrospinning and the applications of these fibers as optical oxygen sensors for both gaseous and dissolved oxygen. A protective ‘shell’ layer of polycaprolactone (PCL) not only maintains the fiber morphology of PDMS du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(55 citation statements)
references
References 47 publications
2
53
0
Order By: Relevance
“…The low porosity could be another explanation to the slow response times of the cast films, in addition to the smaller available surface area for the oxygen molecules to access. Other studies show that increasing film thickness of 2D polymer films increases diffusion depth and correlates to greater oxygen response time [14]. An order of magnitude increase in PCL fiber diameter also reduced sensitivity and increased response time, imposing limits on oxygen diffusion through the polymer matrix [13].…”
Section: Discussionmentioning
confidence: 95%
“…The low porosity could be another explanation to the slow response times of the cast films, in addition to the smaller available surface area for the oxygen molecules to access. Other studies show that increasing film thickness of 2D polymer films increases diffusion depth and correlates to greater oxygen response time [14]. An order of magnitude increase in PCL fiber diameter also reduced sensitivity and increased response time, imposing limits on oxygen diffusion through the polymer matrix [13].…”
Section: Discussionmentioning
confidence: 95%
“…Lannutti et al developed core/shell structured fibers with PCL as shell and oxygen-sensitive probe, tris(4,7-diphenyl-1,10-phenanthroline) ruthenium(II) (Ru(dpp)) and platinum octaethylpor-phyrin (PtOEP) containing polydimethylsiloxane (PDMS) as the core, for oxygen detection. [124] It was found that the sensor exhibited rapid response within 0.5 s due to the porous structure of the nanofibers and the excellent oxygen permeability of PDMS. Table 2 shows the representative electrospun nanofiber-based biosensors for cancer cell detection.…”
Section: Emerging Roles Of Electrospun Nanofibers In Cancer Researchmentioning
confidence: 99%
“…This phenomenon is included in the phenomenon of MLCT. 13 MLCT phenomenon occurs due to ligand has orbital π* with low energy and the presence of MLCT phenomenon on the complex compound cause the complex compound is very well be used as dye sensitizer because it can absorb light with optimal so that it can be converted into electrical energy. When a compound has a lot of electrons in d orbitals and amount of ligand is abundant it cause the compounds are able to suffer the MLCT phenomenon.…”
Section: The Characterization Of Complex Compounds Of Fe(iii)-chloropmentioning
confidence: 99%
“…When a compound has a lot of electrons in d orbitals and amount of ligand is abundant it cause the compounds are able to suffer the MLCT phenomenon. 13 In this study, Fe(III)-chlorophyll dissolved in dimethyl sulfoxide (DMSO) as solvent because this solvent has high degree of polarity. In addition DMSO also not liberate hydrogen when met with very electropositive metal.…”
Section: The Characterization Of Complex Compounds Of Fe(iii)-chloropmentioning
confidence: 99%